Analisis Efektivitas Biaya Penggunaan Pioglitazone Dibandingkan Glimepiride Pada Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Wilayah Kota Mataram - Kholida Zhahara; Diesty Anita Nugraheni; Okti Ratna Mafruhah (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
Diabetes mellitus (DM) is a chronic disease requires long-term therapy, which can result in high medical costs. This study aims to analyze the cost-effectiveness of oral antidiabetic therapy with pioglitazone compared with glimepiride in type 2 diabetes mellitus outpatients at RSI Siti Hajar Mataram and RSUD H. Moh. Roeslan Kota Mataram from the hospital perspective. This research is an observational method with a cross-sectional design. Data were collected with retrospective and concurrent from medical record and treatment cost data of patients from May-Auguts 2025. Data analysis using the average cost-effectiveness ratio (ACER). The subject of this study is type 2 diabetes mellitus outpatients who met the inclusion and exclusion criteria, with patients received pioglitazone monotherapy and combination is 119 patients, while 133 patients received monotherapy and combination of glimepiride. The result showed that pioglitazone monotherapy could achieve a higher therapeutic target (80,82%) and had lower ACER value Rp 7.867,80 than the glimepiride. While the combination therapy of glimepiride-metformin could achieve a higher therapeutic target (78,57%) and had lower ACER value Rp 5.404,50 than the combination of pioglitazone-metformin. The conclusion of this study pioglitazone monotherapy is perceived to be more cost-effective than glimepiride, while the combination of glimepiride-metformin is perceived to be more cost-effective than combination of pioglitazone-metformin.